Voltammetric determination of Diazepam at meniscus-modified silver solid amalgam electrode - Samiec, Petr; Fischer, Jan; Navrátilová, Zuzana (Univerzita Pardubice, 2014)
Voltammetric methods for determination of Diazepam (DZ) were developed. Techniques differential pulse voltammetry and DC voltammetry were used for determination of DZ at meniscus-modified silver solid amalgam electrode (m-AgSAE). The effect of the pH on the intensity of signal of DZ was studied in a mixture of Britton-Robinson buffer + methanol (9:1) and 0.1 M NaOH + methanol (9:1); the optimal medium for analysis was a mixture of 0.1 M NaOH + methanol (9:1). The developed method has been tested on the determination of DZ in a sample of commercial drug (Diazepam).
Keywords: meniscus modified silver solid amalgam electrode; DC voltammetry; differential pulse voltammetry; Diazepam; determination